(untitled) (Medico Legal Update, 2019)
Cardiac Troponin I (cTnI) is a very sensitive biochemical marker for the diagnosis of myocardial infarction (MI) in Sudden Cardiac Death (SCD). cTnI has nearly absolute myocardial tissue specificity, thereby reflecting even microscopic zones of myocardial necrosis. The aim of this study is to find out the gross and microscopic changes in heart and determinants of elevated levels of cTnI in cases of SCD. This cross sectional study was conducted in 50 cases of SCD brought for medicolegal autopsy at Government Medical College, Thiruvananthapuram. Heart was examined for gross and microscopic changes and blood level of cTnI. The mean value of cTnI was 3.4 (sd – 7.8) ng/dl. Age (>50 years), male sex, BMI (>25), previous history of CAD, family history, diabetes mellitus and hypertension were the determinants of level of cTnI in the postmortem blood. Common morphological findings observed in heart were haemorrhage, hypereosinophilia and oedema. From this study it can be concluded that cTnI assay can be used as a valuable supportive measure for postmortem diagnosis of SCD.